The Effect of self-esteem on romantic liking - Walster, Elaine (1965)
It was proposed that a person's momentary self-esteem affects his receptivity to the affection offered by another. People whose self-esteem was temporarily low were expected to like an affectionate, accepting other more than those whose self-esteem was momentarily high.An experimental study was conducted to test this proposal. The selfesteem of one half of the Ss was raised by giving them false personality information; the self-esteem of the other half of the Ss was lowered by the same technique. Women then rated a male confederate, who had earlier asked them for a date. The Ss in the low self-esteem condition expressed significantly more liking for the confederate than did Ss in the high self-esteem condition.The relationship between ?stable? (or measured) self-esteem and liking for others was also discussed.
Includes bibliographical references.
Keywords: Self-esteem.; Interpersonal relation